The Condition of Possibilities for ASEAN in Adopting International Norms Against Sea Piracy - Poetri, Ayu Praditha; Kurniawan, Yandry (Jurnal Politik, 2023)
The shift of sea piracy trend in Southeast Asia, from primordial piracy to contemporary piracy, has happened for a few decades. To ensure the region remains invulnerable, ASEAN as regional institution adopts two international maritime norms into the region to develop the regional norms against sea piracy. Those norms are the UNCLOS 1982 and the Convention for the Suppression of Unlawful Acts against the Safety of Maritime Navigation 1988 and its Protocol for the Suppression of Unlawful Acts against the Safety of Fixed Platforms Located on the Continental Shelf. This paper explores the process of external norms diffusions with the local extant norm using the norm diffusion theory and qualitative research method as the analytical framework. The research finds that ASEAN adopts the international norms with several adjustment especially on the notion of hot pursuit. Considering the sensitive nature of the issue, ASEAN accommodates hot pursuit through legal and law enforcement matter stated on the 2002 Work Plan to Implement ASEAN Plan of Action to Combat Transnational Crimes.